Optimalisasi Kampung Organik sebagai Ketahanan Pangan di Kelurahan Rejowinangun Selatan - Alifia Revan Prananda; Cornelius Rangga Surya Kusuma; Dinda Kusumaningrum; Galih Slamet (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Bay leaves are one of the toga plants (family medicinal plants) which can be used to stop excessive defecation. Apart from that, bay leaves can also be used to treat gout, stroke, high cholesterol, improve blood circulation, stomach inflammation, itching and diabetes. Therefore, there is a need for education in the form of counseling regarding the use of bay leaves and how to process them as herbal medicine to help cure diseases. Kaffir lime is a natural ingredient in various food and beverage products in Indonesia and other Asian countries. Kaffir lime plants contain compounds including essential oils which are also rich in benefits such as antioxidants, antimicrobials, antileuchemicals, antitussives, insecticides, illaricides and phenolic compounds such as flavonoids, flavanones, flavones, flavonols and glycerolipids which according to research function as a source of antioxidants, anti-inflammatory , antiviral, anti-allergic, and anti-carcinogenic, anti-aging for the human body. The planting of kitchen spices in the form of bay plants and orange leaves is grown using organic and environmentally friendly materials.